Quiero ser bombero - Liebman, Daniel (Buffalo, N.Y. : Firefly Books, 2002)
Photographs and easy-to-read text describe the job of a firefighter.
Translation of: I want to be a firefighter.
Accelerated Reader
Keywords: Fire fighters -- Juvenile literature; Fire fighters -- Vocational guidance -- Juvenile literature; Occupations -- Juvenile literature; Bomberos -- Literatura juvenil; Bomberos -- Orientación profesional -- Literatura juvenil; Empleos -- Literatura juvenil